Capitalism, coronavirus, and mental suffering - Ferguson, Iain (Argumentum, 2023)
The COVID-19 pandemic that has ravaged the globe since early 2020 has combined mental health stressors that have been studied before in other disasters, but which have never been seen consolidated in one global crisis. So, for example, there is research on how humans cope with quarantine, mass disasters and ongoing stressors but not on all three. What is clear, however, is that this is not simply a ‘natural’ disaster. The manner in which this pandemic originated, the ways in which it has spread, and the degree of death and devastation which it has wrought upon communities across the globe have all been shaped by far from natural factors such as global capitalism’s relentless drive for profit, the ways in which national governments have responded (or failed to respond) to the spread of the pandemic and the impact of existing divisions and inequalities on rates of infection and death. This applies no less to the short-term and long-term impact of the pandemic on mental health. Mainstream psychiatric approaches which focus on diagnosis and treatment can lead to medicalising or pathologizing what are essentially normal human reactions to traumatic events and to individualising responses to what is in essence a collective and structural crisis. That shared collective experience allows for the possibility of a collective political response, a response which both challenges those responsible for so many avoidable deaths and which also, through promoting a sense of political agency and solidarity, challenges the feelings of powerlessness, shame and isolation associated with mental distress.